2020
DOI: 10.1111/ajt.16188
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of COVID-19 in solid organ transplant recipients: A cohort study

Abstract: Solid organ transplant recipients (SOTr) with coronavirus disease 2019 (COVID‐19) are expected to have poorer outcomes compared to nontransplant patients because of immunosuppression and comorbidities. The clinical characteristics of 47 SOTr (38 kidneys and 9 nonkidney organs) were compared to 100 consecutive hospitalized nontransplant controls. Twelve of 47 SOTr managed as outpatients were subsequently excluded from the outcome analyses to avoid potential selection bias. Chronic kidney disease (89% vs 57% P =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
153
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(172 citation statements)
references
References 31 publications
13
153
2
4
Order By: Relevance
“…Issues that potentially confound the Clarke et al analysis include the retrospective nature and relatively small sample size as well as limitations of accurate identification of true cases. Their data on mortality in kidney transplant recipients are however, similar to those reported by others and with respect to medical risk factors associated with mortality, and the higher proportion of patients from Black and other ethnic minorities ( 6 , 7 ). An important question not addressed in their analysis is how a diagnosis of COVID-19 in waitlisted patients who recover will affect their transplant candidacy and outcomes going forward.…”
supporting
confidence: 82%
“…Issues that potentially confound the Clarke et al analysis include the retrospective nature and relatively small sample size as well as limitations of accurate identification of true cases. Their data on mortality in kidney transplant recipients are however, similar to those reported by others and with respect to medical risk factors associated with mortality, and the higher proportion of patients from Black and other ethnic minorities ( 6 , 7 ). An important question not addressed in their analysis is how a diagnosis of COVID-19 in waitlisted patients who recover will affect their transplant candidacy and outcomes going forward.…”
supporting
confidence: 82%
“…Fever was common in studies, ranging from 52% to 95%; cough ranged from 49% to 78%, and dyspnoea from 28% to 70%. Gastrointestinal symptoms were also reported, as high as 53% in Chaudhry et al 26 Four studies reported data on AKI or graft dysfunction at presentation, ranging from 28% in Mohamed et al to 77% in Chen et al 20 , 27 No report described asymptomatic infection.…”
Section: Resultsmentioning
confidence: 99%
“… 25 - 27 Previously published data in SOT recipients reported fever as the most common presenting symptom. 8 - 11 Chaudhary et al 13 had 55% of SOT recipients with diarrhea on presentation, while 8.4% presented with altered mentation. In our study pulmonary symptoms were the most common presentation, while fever was observed only in 55% of our COVID-19-positive patients.…”
Section: Discussionmentioning
confidence: 99%
“… 7 - 11 Early published data show 16%–20% mortality among COVID-19-positive SOT recipients. 10 - 13 Long-term SOT recipients (transplanted >3 years), particularly those with kidney transplants, are primarily managed by their local healthcare providers with limited expertise in caring for this vulnerable cohort. With the increasing cases in our region and with tertiary centers being at capacity, community providers are increasingly having to care for COVID-19 positive patients.…”
mentioning
confidence: 99%